A clinical study of the immunogenicity and protective potency of a live recombinant GamLPV vaccine for intranasal use for the prevention of whooping cough in adult volunteers - Alevtina A. Lidzhieva; Alisa Yu. Medkova; Sergey V. Kulikov; Ludmila N. Sinyashina; Rezida A. Sioundioukova; Andrey P. Markov; Aleksey B. Verveda; Natalia E. Abaeva; Irina N. Chernyshova; Marina V. Gavrilova; Kristina K. Bushkova; Ilya N. Dyakov; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии, 2024)
Introduction. The increase in incidence rate of pertussis worldwide, short-term insufficient immunity induced by acellular pertussis vaccines (TDaP) and their failure to provide antibacterial protection and to prevent transmission of infection in human population dictate the development of new pertussis vaccines. A new live recombinant pertussis vaccine for intranasal use (GamLPV) has completed preclinical studies in experiments on nonhuman primates and 2 phases of clinical trials involving adult healthy volunteers, in which the safety, immunogenicity and protective activity of the GamLPV were proven. Method and scheme of vaccine administration have been worked out.